Cerebral hemispheres – cerebellum – kidney interaction in patients with acute cerebral ischemia - Kononets , O.M.; Tkachenko, O.V.; Kamenetska, O.O. (Medicni Perspektivi, 2021)
The nervous system, in particular the autonomic one, is well known to constantly regulate the internal functioning of the body, adapting it to changeable external and internal environmental parameters. In particular, there is a close multiple-vector correlation between the nervous system and the kidneys. The aim of this study was to specify the mechanisms, clinical and paraclinical characteristics of the concomitant lesions of the nervous system and the kidneys in patients with acute stroke. This paper presents the case report of 215 patients, aged 70 ± 8.44, who suffered from ischemic stroke. Among them, we examined 144 women and 71 men. The patients underwent a comprehensive examination, including a detailed clinical and neurological check-up (evaluating the patients’ condition severity with the National Institutes of Health Stroke Scale (NIHSS) and the Barthel index on admission and on the 21st day of the disease), laboratory analysis (electrolyte balance, nitrogen metabolism (on admission and on the 21st day of the disease) and instrumental examination (CT scan of the brain, the follow-up brain magnetic resonance imaging). The statistical methods were used to analyze the data. In the 1st day of the disease, all the surveyed patients with right hemispheric carotid stroke and the overwhelming majority of the patients with left hemispheric carotid stroke and ischemic stroke in the vertebrobasilar system had cerebral renal syndrome, represented by renal concentration-filtration dysfunction, accompanied by the reduced glomerular filtration rate. A reliable relationship was found between the renal concentration and filtration function and the right hemispheric ischemic focus in patients with ischemic stroke, the characteristics are to be specified.